Assessment of Etiological Factors for the Incidence of Polycystic Ovary Syndrome/Polycystic Ovary Disease and the Pharmacists Review on Treatment Protocols – A Comprehensive Prospective Observational Study - Latha, S. Swarna (Asian Journal of Pharmaceutics (AJP), 2025)
This study aimed to evaluate the prevalence and contributing factors of Polycystic Ovary Syndrome (PCOS) and Polycystic Ovary Disease (PCOD) among women, along with their awareness levels and the role of pharmacists in management. Methodology: A prospective observational study was conducted at the Maharaja Institute of Medical Sciences (MIMS), Vizianagaram, from November 2024 to February 2025. A total of 100 female patients from the Department of Gynaecology and Obstetrics were included, based on the Rotterdam diagnostic criteria.Data were collected using a standardized questionnaire covering demographic details, clinical symptoms, awareness levels, and pharmacist interventions. Statistical analysis employed descriptive methods (mean, standard deviation, percentages) and inferential tests, including ANOVA to examine associations between demographic/clinical factors and disease severity. A p-value <0.05 was considered significant. Results: Among the participants, 47 were diagnosed with PCOS and 53 with PCOD. A significant portion (53%) had limited or no awareness about their condition. Irregular menstruation (85%), heavy bleeding (71%), and scalp hair loss (74%) were common symptoms. Most women (48%) had normal BMI, while 36% were overweight and 12% obese. Urban residents showed a higher prevalence. Pharmacist interventions addressed drug-related issues in 18% of cases. The analysis indicated statistically significant associations between symptoms and disease severity (p < 0.05). Conclusion: The findings highlight the increasing burden of PCOS/PCOD, especially among young adult women. Poor awareness contributes to delayed diagnosis, while pharmacists play a key role in patient education, side-effect management, and lifestyle modification support.Strengthening early intervention, awarenessand active pharmacist involvement can improve outcomes